Improving Problem Solving Skills of High School Students using Online Discovery Learning in Chemical Equilibrium - Rosilawati, Ila; Kadaritna, Nina; Setyarini, M. (FKIP Universitas Lampung, 2022)
This research was aimed to describe the improvement of students problem solving skills through discovery learning and student readiness in online learning. This study is a quasi experimental design using a nonequivalent pretest-posttest control group design. The population were all students of class XI MIPA SMAN 3 Bandar Lampung. The sampling technique used purposive sampling. Problem solving skills, student readiness in online learning were analyzed by independent t-test and correlation test. The results showed: (1) discovery learning is effective to improve problem solving skills on chemical equilibrium material; (2) there is a significant relationship between self-control and problem solving skills; (3) there is a significant relationship between the efficacy of using the internet in online learning with problem solving skills; (4) there is a significant relationship between self-control and the efficacy of using internet in online learning with problem solving skills. Keywords: online learning, student readiness, problem solving skills, discovery learning. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp400-409